Erlotinib plus bevacizumab as an effective treatment for leptomeningeal metastases from EGFR mutation-positive non-small cell lung cancer. (September 2016) - Sakata, Yoshihiko; Kawamura, Kodai; Shingu, Naoki; Ichikado, Kazuya
Highlights: Leptomeningeal metastasis is a severe complication of non-small cell lung cancer. Prognosis of leptomeningeal metastasis is poor and treatment efficacy is limited. EGF receptor-tyrosine kinase inhibitors have high response rates. Erlotinib + bevacizumab can treat leptomeningeal metastases in EGFR -positive cases. Cerebrospinal fluid penetration rates of erlotinib are improved with bevacizumab. Abstract: Leptomeningeal metastasis is a severe complication of non-small cell lung cancer. Its prognosis is very poor and conventional treatments have limited efficacy. However, epidermal growth factor receptor-tyrosine kinase inhibitors have exhibited high response rates in EGFR mutation-positive lung cancer patients with central nervous system metastases. It has been postulated that this could be due to the penetration of agents into the central nervous system and a high cerebrospinal fluid concentration is a key consideration in measuring treatment effect. Bevacizumab has also been used as an effective therapeutic agent in patients with central nervous system metastases. However, the efficacy of epidermal growth factor receptor-tyrosine kinase inhibitor doublet therapy for leptomeningeal metastases and the cerebrospinal fluid penetration of epidermal growth factor receptor-tyrosine kinase inhibitors have yet to be determined. Moreover, the safety of this doublet regimen in patients with a poor general condition is not known. Herein, we report on a case treated with erlotinib plus bevacizumab for leptomeningeal metastases from EGFR mutation-positive non-small cell lung cancer. The patient's performance status significantly improved and the cerebrospinal fluid penetration rate of erlotinib plus bevacizumab was equal to or greater than the past reports of erlotinib alone.